Handbook of organic food procesing and production (Blackie Academic Professional, 1994)
An initial introduction to organic food is followed by a review of organic legislation (chapter 2) and organic certification process(chapter 3). The following six chapters cover the major organic commodity groups: Fruit and Vegetables, Cereal Products, Meat and Meat Products, Dairy Products, Other Processed Foods and Alcoholic Drinks. Chapter 10 is devoted to developments in USA. Finally, there is an extensive directory, giving details of the major players and organic organisations throughout the world